2020
DOI: 10.1093/noajnl/vdaa137
|View full text |Cite
|
Sign up to set email alerts
|

Improved risk stratification in youngerIDHwild-type glioblastoma patients by combining a 4-miRNA signature withMGMTpromoter methylation status

Abstract: Background The potential benefit of risk stratification using a 4-miRNA signature in combination with MGMT promoter methylation in IDH1/2 wild-type glioblastoma patients was assessed. Methods Primary tumors from 102 patients with comparable treatment from the LMU Munich (n=37), the University Hospital Düsseldorf (n=33) and The Cancer Genome Atlas (TCGA, n=32) were included. Risk groups were built using expressions of hsa-let-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The trial also includes several secondary endpoints, including treatment safety and tolerability of the treatment, PFS, quality of life assessment, and evaluation of cognitive function. In addition to these endpoints, there is a translational exploratory objective in the study to validate a 4-micro-ribunucleoid-acid (4-miRNA) signature-based risk subgroup classification [23] , [24] . This objective aims to investigate the potential of a specific 4-miRNA signature in predicting treatment response or prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The trial also includes several secondary endpoints, including treatment safety and tolerability of the treatment, PFS, quality of life assessment, and evaluation of cognitive function. In addition to these endpoints, there is a translational exploratory objective in the study to validate a 4-micro-ribunucleoid-acid (4-miRNA) signature-based risk subgroup classification [23] , [24] . This objective aims to investigate the potential of a specific 4-miRNA signature in predicting treatment response or prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…To name but a few, Yuan et al suggested a 3-miRNA signature (hsa-miR-222, hsa-miR-302, hsa-miR-646) as a predictor of overall survival (OS), utilizing miRNA expression data for GBM patients from the Cancer Genome Atlas (TCGA) dataset [ 8 ]. A recently published 4-miRNA signature showed prognostic value, taking into account MGMT promoter methylation and age as cofactors, in IDH1/2 wild type GBM patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%